Peculiarities of primary education and musical and aesthetic education in the conditions of the korean war of 1950-53. Recollections of witnesses and notes on the cover of the textbook - Kim, Oleksandr; Tkachenko, Maryna (Professional Art Education, 2026)
Purpose of the study: to search the conditions of primary and secondary education organization, including concerning a subject "Music" during the Korean war. Objects of research: The memoirs of the eyewitnesses, list and analysis of some songs submitted in the textbook of music for primary school of a sample of 1950, including notes of the schoolboy on a cover of the textbook. The circumstances of the Korean War of 1950-53 and the features of primary education, including musical and aesthetic education, have been almost not studied in the scientific literature in Ukraine. The content of government directives and the list of topics in school programs are mainly highlighted. In view of this, it is important to study living witnesses of the events, analyze texts in textbooks, as well as the conditions for implementing the educational process.Results: The memories of witnesses of the first days of the Korean War, the features of school classes "in the open air" were studied. The list of songs in the 1950 music textbook was analyzed. The lyrics of some songs were given. The facts from history, reflected in the student's notes on the cover of the textbook, were studied.Conclusions: The state and civil society in the conditions of a brutal war demonstrated resilience and cohesion in ensuring the educational process. It is advisable to further study this experience in detail.
Keywords: Korean War; primary education; musical and aesthetic education; textbook; eyewitness accounts; reintegration